Fundamentals and new frontiers of Bose-Einstein condensation - Ueda, Masahito (World Scientific, 2010)
This book covers the fundamentals of and new developments in gaseous Bose–Einstein condensation. It begins with a review of fundamental concepts and theorems, and introduces basic theories describing Bose-Einstein condensation (BEC). It then discusses some recent topics such as fast-rotating BEC, spinor and dipolar BEC, low-dimensional BEC, balanced and imbalanced fermionic superfluidity including BCS-BEC crossover and unitary gas, and p-wave superfluidity.